Pengaruh Organizational Citizenship Behavior Terhadap Kinerja Pegawai Di Kantor Kecamatan Banjarmasin Utara - Fadly, Fadly; Ansori, Muhammad; Aldhalia, Dhena (Jurnal Publisitas, 2021)
This study aims to explore the influence of Organizational Citizenship Behavior (OCB) on employee performance in the North Banjarmasin District Office. It is hoped that this study will be useful for government organizations in the form of data related to the influence of Organizational Citizenship Behavior (OCB) with respect to employee performance in the North Banjarmasin District Office. This study is an associative research with quantitative methods. Data was collected using field survey methods and distributed questionnaires to all employees of the North Banjarmasin District Office. Theory references from the internal organs regarding the factors that influence Organizational Citizenship Behavior (OCB). The results of data analysis in this study using validity and reliability tests with the SPSS version 22 program are valid and reliable. The information is analyzed using simple regression analysis, the coefficient of determination test and the t test. It can be concluded that there is an influence of Organizational Citizenship Behavior (OCB) on the performance of employees in the North Banjarmasin District Office. This can be evidenced by the significance of a = 0.05 which where the test results and their significance t = 6.203 <0.05 (0.000 <0.05) means that the hypothesis can be said that Ho rejected and Ha accepted. So, the conclusion is that the Organizational Citizenship Behavior (OCB) has a significant effect on employee performance in the North Banjarmasin District Office. Suggestions from this study are expected to be able to create a culture of behavior and conditions Organizational Citizenship Behavior for employee(OCB) in order to increase the productivity of human resources in increasing productivity.